From traditional evaluation to evaluation with the Corubrics digital tool - Zambrano Mendoza, Jose Reynaldo; Yánez Rodríguez, Marcos Alejandro; Gámez, María Rodríguez (International Journal of Psychosocial Rehabilitation, 2020)
The use of Information and Communication Technologies together with their digital tools have evolved in all spheres of the current community while continuing to take into account the educational field and the use of a non-traditional methodology through digital rubrics. This advancement in technology has created environments that favor interaction between teacher and student. In recent years, new digital trends such as rubrics have emerged, based on a set of standards and parameters that improve individual assessment, among peers, strengthening collaborative learning. The use of the rubrics seemed to us a very opportune instrument for the evaluation of tasks, expositions, teamwork, since it measures the degree of performance of student achievements and facilitates the feedback process essential for learning. The research methodology used is the bibliographic review method related to the use of information and communication technologies in order to demonstrate the utility of the Corubrics tool for the design of digital rubrics for greater interactivity in the evaluation process.